1996
DOI: 10.1002/j.1460-2075.1996.tb00973.x
|View full text |Cite
|
Sign up to set email alerts
|

STK/RON receptor tyrosine kinase mediates both apoptotic and growth signals via the multifunctional docking site conserved among the HGF receptor family.

Abstract: STK/RON tyrosine kinase, a member of the hepatocyte growth factor (HGF) receptor family, is a receptor for macrophage‐stimulating protein (MSP). To examine the STK/RON signalling pathway, we generated STK/ RON transfectants showing opposite features in growth. STK/RON‐expressing Ba/F3 pro‐B cells (BaF/STK) exhibited MSP‐dependent growth, whereas STK/ RON‐expressing mouse erythroleukaemia cells (MEL/ STK) displayed MSP‐induced apoptosis. This apoptosis was accompanied by the prolonged activation of c‐Jun N‐term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
99
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 56 publications
2
99
0
Order By: Relevance
“…The observation that sfRon, with its intrinsic oncogenic potential, is also present in normal tissues (Ronsin et al, 1993;Gaudino et al, 1994;Iwama et al, 1996) led us to speculate; but further studies are required, that sfRon might be preferentially expressed in rapidly growing cells during normal development or adult tissue renewal, whereas the ratio of both forms would control tissue homeostasis. In the tumor cells, this ratio could be tilted toward driving proliferation, invasion and rapid tumor growth.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The observation that sfRon, with its intrinsic oncogenic potential, is also present in normal tissues (Ronsin et al, 1993;Gaudino et al, 1994;Iwama et al, 1996) led us to speculate; but further studies are required, that sfRon might be preferentially expressed in rapidly growing cells during normal development or adult tissue renewal, whereas the ratio of both forms would control tissue homeostasis. In the tumor cells, this ratio could be tilted toward driving proliferation, invasion and rapid tumor growth.…”
Section: Discussionmentioning
confidence: 97%
“…Human sfRon mRNA was detected at low levels in several normal adult organs such as colon, skin and lung (Ronsin et al, 1993;Gaudino et al, 1994;Iwama et al, 1996) as well as in lung cancer , erythroleukemia (Bardella et al, 2004) and gastric cancers (Gaudino et al, 1994). Bardella et al (2004) showed that epithelial cells transduced with sfRon display an aggressive phenotype and shift to a nonepithelial morphology; they grow faster, become motile and are unable to form aggregates.…”
Section: Introductionmentioning
confidence: 99%
“…Ron is expressed in cells of di erent origin: epithelial cells (Gaudino et al, 1994;Medico et al, 1996), neuroendocrine cells (Gaudino et al, 1995), osteoclasts (Kurihara et al, 1996) and hematopoietic cells (Banu et al, 1996;Iwama et al, 1996). Its overexpression in a signi®cant fraction of primary breast carcinomas suggests a correlation with progression of mammary tumors (Maggiora et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Other phosphorylation sites correspond to tyrosine residues located outside the kinase domain and have the important function of creating docking sites for SH2-containing molecules. In Met and Ron, two tyrosines in the tail (in Met: Y1349/Y1356 and in Ron Y1353/Y1360) are part of the multifunctional docking site responsible for association with signal transducers Iwama et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been demonstrated that Ron7/7 mice display a deregulated in¯ammatory response (Correll et al, 1997). Ron mediates mitogenic and apoptotic responses, as well as motility by signalling through a multi-functional docking site, conserved in the evolutionary related receptors Met and Sea (Ponzetto et al, 1994;Iwama et al, 1996;Wang et al, 1996).…”
Section: Introductionmentioning
confidence: 99%